Effect of electron correlation on positronium formation in positron-helium scattering - Chaudhuri, P. [UNESP]; Adhikari, S. K. [UNESP]; Talukdar, B.; Bhattacharyya, S. (Springer, 1999)
A three-parameter correlated wave function for the helium ground state is used to study the scattering reaction e(+) + He --> He+ + Ps, where Ps stands for positronium atom. An exact analytical expression is constructed for the first Born scattering amplitude for Ps formation from helium. Based on this numerical results are presented for both differential and total cross-sections. It is demonstrated that the inner electronic correlation of the target atom plays a crucial role in explaining the discrepency between theory and experiment.